Como cachorros e máquinas: superexploração em maquiadoras têxteis do alto paraná - paraguai - Cardozo, Victor Hugo Jara (2022)
Despite the fact that the maquiladora activity in Paraguay has begun to develop since the beginning of this century, it is still a subject little addressed by the academic community. It consists of a modality of foreign investment with a special tax regime, through which it can import all the necessary elements for production without paying tax rates and must subsequently export all the merchandise produced. The present work has been oriented from two general objectives, these are, the characterization of the maquila in the context of global and Latin American economic development, on the one hand, and, on the other, the study of working conditions in the textile maquiladoras in the department of Alto Paraná – Paraguay. The theoretical framework on which the work is sustained is the Marxist Dependency Theory (TMD), especially the proposal of Ruy Mauro Marini from whom we take various concepts such as the super-exploitation of work. In the first part of the work, a brief review of Latin American economic development and the international context where the maquila has emerged has been carried out in such a way as to understand the global and local articulations that intervene in the maquila. In the second part, continuity is given with an analytical description of the working conditions based on data collection from a primary source. A total of 22 in-depth semi-structured interviews have been carried out with workers and other relevant stakeholders. The sampling technique used was non-probabilistic for convenience and the sample size has followed the orientation of Salgado (2012). The result of the investigation has revealed that, firstly, the maquila is part of the restructuring process of the world economy in the context of the structural crisis of capitalism in the mid-1970s, secondly, that the conditions of Work in the textile maquilas in Alto Paraná are precarious, characterized mainly by high levels of circulation, intensity, and mistreatment. From this, it is concluded that there is not enough evidence to sustain that the maquila can generate a process of integral industrial development and that the working class reproduces itself in conditions of super- exploitation of work.